2008
DOI: 10.1002/art.23418
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the chondrogenic potential of human synovial stem cells according to harvest site and culture parameters in knees with medial compartment osteoarthritis

Abstract: Objective. Synovial mesenchymal stem cells (MSCs) are an attractive cell source for cartilage regeneration because of their high chondrogenic ability. In this study, we examined the synovium of patients with medial compartment knee osteoarthritis (OA) to determine the proportion of MSCs in relation to cellular compartmentalization, and to identify the culture parameters that could affect the chondrogenic potential of synovial MSCs.Methods. Human synovium was collected from 4 different harvest sites in the knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 41 publications
8
75
0
1
Order By: Relevance
“…It is suggested that neo-cartilage in 3D culture is observed after 14-21 days of continuous culture. Together with the previous literature, this refl ected the fact that the duration of our 3D culture was too short to allow re-differentiation from the monolayer culture of ACs and SYs passaged continuously (Nagase et al, 2008;Zhang et al, 2004). Furthermore, our system can yield mass production of transplantable chondrogenic tissue.…”
Section: Spheroids Of Synovium-derived Cells and Chondrocytessupporting
confidence: 54%
See 1 more Smart Citation
“…It is suggested that neo-cartilage in 3D culture is observed after 14-21 days of continuous culture. Together with the previous literature, this refl ected the fact that the duration of our 3D culture was too short to allow re-differentiation from the monolayer culture of ACs and SYs passaged continuously (Nagase et al, 2008;Zhang et al, 2004). Furthermore, our system can yield mass production of transplantable chondrogenic tissue.…”
Section: Spheroids Of Synovium-derived Cells and Chondrocytessupporting
confidence: 54%
“…their high proliferative capacity and chondrogenic potential ( Sakaguchi et al, 2005;Yoshimura et al, 2007;Nagase et al, 2008;.…”
Section: Spheroids Of Synovium-derived Cells and Chondrocytesmentioning
confidence: 99%
“…Cell fluorescence was evaluated by FACSCalibur instrument (Becton Dickinson), and data were analyzed using CellQuest software (Becton Dickinson). 11,15 Chondrogenesis Two hundred thousands cells at passage 2 were placed in a 15-ml polypropylene tube (Becton Dickinson) and centrifuged at 450 g for 10 min. The pellets were cultured at 371C with 5% CO 2 in 400 ml chondrogenic media that contained 500 ng/ml bone morphogenetic protein 2 (Astellas Pharm, Tokyo, Japan), 10 ng/ml transforming growth factor-b3 (R&D Systems, Minneapolis, MN, USA), 100 nM dexamethasone, 50 mg/ml ascorbate-2-phosphate, 40 mg/ml proline, 100 mg/ml pyruvate (Sigma-Aldrich), and 50 mg/ml ITS þ Premix in high-glucose Dulbecco modified Eagle medium (Invitrogen).…”
Section: Surface Epitopesmentioning
confidence: 99%
“…The medium was replaced every 3-4 days for 21 days. [15][16][17][18] Histology The cultures were ended by fixing the pellets with 2.5% glutaraldehyde in 0.1 M PBS for 2 h. The cells were washed overnight at 41C in the same buffer and post-fixed with 1% OsO4 buffered with 0.1 M PBS for 2 h. The pellets were dehydrated in a graded series of ethanol and embedded in Epon 812. Semi-thin (1 mm) sections for light microscopy were collected on glass slides and stained for 30 s with toluidine blue.…”
Section: Surface Epitopesmentioning
confidence: 99%
“…SDSCs maintain their chondrogenic capacity regardless of donor age or disease condition (De Bari et al, 2001;Nagase et al, 2008) and have potential for tissue-engineering applications aimed at cartilage repair or regeneration (Bilgen et al, 2007;Han et al, 2010;Lima et al, 2007;Pei et al, 2008a;Pei et al, 2008b). We previously cultured SDSCs in a 3D hydrogel which achieved properties approaching those of native juvenile bovine cartilage.…”
Section: Introductionmentioning
confidence: 99%